The interplay of workload, stress, and competence: enhancing performance through work culture - Nanang Setiawan; Ginta Ginting; Meirani Harsasi (Insight Management Journal, 2026)
This study aims to analyze the effect of workload, competence, and work stress on employee performance at the Directorate of Academic Administration and Graduation (DAAK) of Universitas Terbuka, as well as to examine the role of work culture as a moderating variable. This research uses a descriptive and correlational quantitative approach with a saturated sample of 75 employees. Data analysis was conducted using Partial Least Square - Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that competence has a positive and significant effect on improving employee performance, while workload and work stress do not have a direct significant effect on performance. Furthermore, work culture is empirically proven to moderate the impact of workload and work stress on employee performance, but does not moderate the relationship between competence and performance. Based on these findings, management is highly recommended to continuously invest in employee technical competence development programs and maintain a positive work culture climate to mitigate the effects of operational stress. For future studies, it is recommended to expand the research object to other units and explore additional variables such as leadership or job satisfaction.